Experimental Study of the Performance of a Horizontal Axis Wind Turbine with A Flat Taper Type of 4:5 and an Outer Angle of 25° With Variations in The Number of Blades - Anandia, Faranita Putri; Sahid, Sahid; Roihatin, Anis (Politeknik Negeri Semarang, 2025)
This experimental study investigates the performance of a Horizontal Axis Wind Turbine (HAWT) with a flat taper 4:5 blade design and a 25° exit angle, focusing on the effect of varying the number of blades (6, 9, and 12). The turbine, with a diameter of 1.1 m and blade dimensions of 470 mm length, 110 mm top width, and 137 mm bottom width, was tested at wind speeds of 3 m/s, 5 m/s, 7 m/s, and 9 m/s in a laboratory setting. Parameters such as wind speed, turbine rotation, voltage, and current were measured to analyze system efficiency. The results indicate that blade count and wind speed significantly influence efficiency. The highest efficiency of 12.51% was achieved at 3 m/s with 9 blades, while at 5 m/s, the efficiency peaked at 3.95% with 9 blades. For higher wind speeds (7 m/s and 9 m/s), the optimal efficiency decreased to 2.03% and 0.95%, respectively, both achieved with 6 blades. The study concludes that this turbine design is most effective at low wind speeds (≤5 m/s), making it suitable for regions with similar wind conditions, such as Indonesia. The findings contribute to optimizing blade configurations for small-scale wind energy applications.